qanda-logo
search-icon
Símbolos
Problema
solution-image
$\left(x+11\right)\left(x-11\right)$ %3D $x^{2}+7x+6=$ $\left(3x+4\right)\left(3x-4\right)$ = $x^{2}+10x+16=$ $\left(a+b\right)\left(a-b\right)$ %3D x2 $-3x-10=$ $\left(x+7\right)\left(x+9\right)$ = $x^{2}+18x+81=$ $\left(2x+1\right)\left(2x+3\right)$ %= 3D $a^{2}+10x+25=$ $\left(x+5\right)\left(x-4\right)$ %3D $x^{2}+2xv+v^{2}$ = $\left(a+10\right)^{2}$ = $x^{2}-100=$ (b $-5\right)^{2}$ = $-1=$ $\left(2x-6y\right)^{2}$ = 9x2 – $36y^{2}$ =
Bachillerato
Aritmética y álgebra
Búsquedas: 127
Solución
answer-user-profile-image
Profesor de Qanda - Rodoalpha
answer-reply-image
Problemas similares